MEKANISME PENCALONAN DAN PENGISIAN JABATAN PRESIDEN DAN WAKIL PRESIDEN YANG DEMOKRATIS DAN KONSTITUSIONAL - Widya Hartati; Ratna Yuniarti (Media Keadilan: Jurnal Ilmu Hukum, 2020)
This study discusses the implementation of the State namely the election of President and Vice President through the general election process (Election). Election is a peaceful process of changing power carried out in accordance with the principles outlined in the constitution. On the other hand, the implementation is not yet democratic and of good quality. This research is a normative legal research, and uses descriptive qualitative analysis. The results of this study indicate that the mechanism for nominating and filling the positions of President and Vice President, is considered still contrary to the principle of popular sovereignty, unconstitutional, violating the principles of democracy and the constitutional rights of political parties and citizens. The mechanism for nominating and filling the positions of President and Vice President will be more democratic if, carried out through political parties and individual channels. For the nomination of the President and Vice President of the Individual Track, in the 2019 simultaneous elections, not a single candidate had passed through the requirements. On the other hand the great expectations of the people so that the Indonesian General Election can be more democratic and the leaders produced are truly from the people, by the people, for the people. Representation through political parties and individual candidates is one mechanism in producing quality leaders.Keywords: constitutional, democratic, presidential election and vice presidentABSTRAKPenelitian ini membahas tentang penyelenggaraan Negara yaitu pemilihan Presiden dan Wakil Presiden melalui proses pemilihan umum (Pemilu). Pemilu merupakan proses pergantian kekuasaan secara damai yang dilakukan sesuai dengan prinsip-prinsip yang digariskan oleh konstitusi. Disisi lain, pelaksanaannya belum demokratis dan berkualitas. Penelitian ini merupakan penelitian hukum normatif, dan menggunakan analisis deskriptif kualitatif. Hasil penelitian ini menunjukkan bahwa mekanisme pencalonan dan pengisian jabatan Presiden dan Wakil Presiden, dinilai masih bertentangan dengan prinsip kedaulatan rakyat, inkonstitusional, melanggar prinsip-prinsip demokrasi dan hak-hak konstitusional partai politik maupun warga negara. Mekanisme pencalonan dan pengisian jabatan Presiden dan Wakil Presiden akan lebih demokratis bila, dilakukan melalui jalur partai politik dan jalur perseorangan. Untuk pencalonan Presiden dan Wakil Presiden Jalur Perseorangan, pada pemilu serentak tahun 2019, belum ada satu calon pun yang berhasil lolos melalui persyaratan. Disisi lain besar harapan rakyat agar Pemilihan Umum Indonesia bisa lebih demokratis dan pemimpin yang dihasilkan benar-benar dari rakyat, oleh rakyat, untuk rakyat. Keterwakilan melalui partai politik dan calon perseorangan merupakan salah satu mekanisme dalam menghasilkan pemimpin yang berkualitas.Kata kunci: demokratis, konstitusional, pemilu presiden dan wapres